On Islamic banking, performance and financial innovations - Bellalah, Mondher (Cambridge Scholars Publishing, 2014)
Islamic banking has seen rapid growth during the last two decades. This is a result of the liberalization of financial regulation, the globalization of financial markets, technological changes, product innovation, the birth of several new Islamic States, and a growing Islamic presence in the West, among other factors.